Mapping the Galaxy in 3D Using Observations of HII Region Absorption with the MWA - Su, Hongquan (Curtin University, 2022)
This thesis measures the distribution of the diffuse synchrotron emission in the Galactic Plane using data from the GaLactic and Extragalactic All-sky MWA survey (GLEAM) in the frequency range 72-231 MHz. It improves the method of calculating the synchrotron emissivity along sight lines intersecting HII regions, and increases the number of such measurements from tens to hundreds. A further 588 HII regions are identified using both their emission and absorption features in the GLEAM maps.